2019
DOI: 10.1177/1535370219828692
|View full text |Cite
|
Sign up to set email alerts
|

Mutual promotion of FGF21 and PPARγ attenuates hypoxia-induced pulmonary hypertension

Abstract: Fibroblast growth factor 21 (FGF21), a primarily liver-derived endocrine factor, has the beneficial effect of protecting blood vessels. Peroxisome proliferator-activated receptor γ (PPARγ), a ligand-activated nuclear transcription factor, has been reported to effectively inhibit pulmonary hypertension (PH). The purpose of this study is to investigate the role of FGF21 in hypoxia-induced PH (HPH) and explore the relationship between FGF21 and PPARγ in this disorder. Adult C57BL/6 mice were subjected to four wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 36 publications
5
29
1
Order By: Relevance
“…We did indeed demonstrate increased FGF-21 mRNA expression in lung tissue from patients with IPAH, but whether this contributes to the elevated circulating FGF-21 levels, rather than simply acting in an autocrine manner, remains to be elucidated. Our finding in human IPAH is in contrast with the results of two preclinical studies which demonstrated that hypoxia-induced PH in mice or rats was associated with decreased FGF-21 mRNA expression in lungs and pulmonary arterioles [ 39 ] or decreased circulating FGF-21 serum levels, respectively [ 40 ]. Interventional studies showed that exogenous FGF-21 attenuated hypoxia-induced PH and inflammatory cytokine secretion through enhancing PPARγ expression in rats [ 40 ], attenuated hypoxic pulmonary arterial remodeling and collagen deposition in mice [ 39 ], and ameliorated hypoxia-induced dysfunction in human pulmonary arterial endothelial cells through alleviating endoplasmic reticulum stress [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We did indeed demonstrate increased FGF-21 mRNA expression in lung tissue from patients with IPAH, but whether this contributes to the elevated circulating FGF-21 levels, rather than simply acting in an autocrine manner, remains to be elucidated. Our finding in human IPAH is in contrast with the results of two preclinical studies which demonstrated that hypoxia-induced PH in mice or rats was associated with decreased FGF-21 mRNA expression in lungs and pulmonary arterioles [ 39 ] or decreased circulating FGF-21 serum levels, respectively [ 40 ]. Interventional studies showed that exogenous FGF-21 attenuated hypoxia-induced PH and inflammatory cytokine secretion through enhancing PPARγ expression in rats [ 40 ], attenuated hypoxic pulmonary arterial remodeling and collagen deposition in mice [ 39 ], and ameliorated hypoxia-induced dysfunction in human pulmonary arterial endothelial cells through alleviating endoplasmic reticulum stress [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, PPARγ has been demonstrated to suppress inflammatory cytokine levels in hypoxia-exposed pulmonary artery smooth muscle cells (20). Recently, hypoxia-induced PH was found to be associated with the reductions in PPARγ expression, and the activation of PPARγ attenuated increased pulmonary arterial pressure and right ventricular hypertrophy in hypoxia-exposed mice (9). The aforementioned findings suggest the protective role of PPARγ in PAH.…”
Section: Discussionmentioning
confidence: 89%
“…Increasing evidence indicates that PPARγ is a potent, protective regulator of PAH (6) and pulmonary artery Ecs (PAECs) (7,8). In addition, a previous study proved that PPARγ activation alleviated hypoxia-induced pulmonary arterial remodeling and collagen deposition in hypoxia-induced PAH (9). However, the role of PPARγ in Ec dysfunction and inflammation in hypoxia-exposed human PAECs (HPAECs) has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that adipose tissue lipolysis is associated with tissue hypoxia (Mahat et al, 2016), which is a pathophysiological state existing in many disease conditions (Famulla et al, 2012;Plihalova et al, 2016;Zhang et al, 2017). At molecular level, lipolysis and hypoxia have been linked to fibroblast growth factor 21 (FGF21), respectively (Arner et al, 2008;Cai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating FGF21 levels have been found to be elevated in patients and experimental animals with various metabolic conditions, such as obesity (Dushay et al, 2010), non-alcoholic fatty liver disease (Kim et al, 2015), and type 2 diabetes (Barb et al, 2019). Besides, previous studies have demonstrated that there was a association between hypoxia and FGF21 regulation in many diseases such as type 2 diabetes with early renal injury (Yu et al, 2019), pulmonary hypertension (Cai et al, 2019), and cerebral disease (Wang et al, 2019). Hypoxic conditions increase the circulating concentrations of FFAs, which are produced from adipose tissue by increased lipolysis (Yin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%